Brachytherapy in vaginal cancer for organ preservation: Clinical outcome and safety from a single center experience - Merten, Ricarda; Strnad, Vratislav; Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schweizer, Claudia; Fietkau, Rainer; Schubert, Philipp (Gynecologic Oncology, 2024)
Background: Interstitial and/or intracavitary brachytherapy is an integral part of the treatment of vaginal cancer Brachytherapy (BT) has shown to improve local control, overall survival (OS) and disease-free survival (DFS). The aim of our study was to analyze the efficacy and safety of brachytherapy in patients with vaginal cancer. Materials and methods: Between 2000 and 2023, 27 patients with vaginal cancer in stage FIGO I-III were treated with brachytherapy with or without external beam radiotherapy (EBRT) and simultaneous chemotherapy. Brachytherapy has been performed either as PDR-brachytherapy alone with a median cumulative dose up to 62.5 Gy (EQD2 = 63.9 Gy) or with PDR-BT boost with median dose of 30.9 Gy (EQD2 = 30.4 Gy). HDR-BT was administered solely as boost with a median dose of 25.5 Gy (EQD2 = 47.8 Gy). The median dose of EBRT was 48.7 Gy and 49.4 Gy for primary and for pelvic lymph nodes. Results: Median follow-up was 39 months (2−120). 5/27 patients developed local recurrences and the 5-year cumulative local recurrence rate for whole patient population was 18.5%. 5-year OS and DFS was 90% and 68%. 5-year DFS for Stage I-II was 72% and for Stage III 65% (p = 0.933). Grade 3 late side effects of brachytherapy were documented in 3/22 patients (13.6%), one patient experienced Grade 4 toxicity (4.5%). Conclusion: Brachytherapy with or without EBRT and concomitant chemotherapy for vaginal cancer is a safe and effective treatment option with excellent local control and overall survival and acceptable toxicity.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Brachytherapy; Dose-escalation; Organ-sparing; Vaginal cancer